Integration of FRP sheet as internal reinforcement in reinforced concrete beam-column joints exposed to sulfate damaged. (June 2021) - Al-Rousan, Rajai Z.; Sharma, Akanshu
Abstract: This paper presents the efficiency of the fiber-reinforced polymer (FRP) composites as internal reinforcement in rescue the structural performance and controlling the mode of failure of the sulfate damaged reinforced concrete (RC) beam-column joint by nonlinear finite element analysis (NLFEA). Firstly, the RC beam-column model was validated against the published experimental results and then was expanded to consider the effect of column axial load level (0%, 25%, 50%, and 75%) and sulfate damage level (without (Level 0), 73 days (Level 1), and 123 days (Level 2)) on the models with and without FRP composites. The structural performance was evaluated in terms of mode of failure, stress distribution, pulling and pushing ultimate load capacity and corresponding displacement, horizontal load–displacement hysteretic loops, horizontal load–displacement envelopes, displacement ductility, energy dissipation, and stiffness degradation. The NLFEA results showed that the internal strengthening of sulfate damaged RC beam-column joint with FRP composite enhanced the cyclic performance (higher load capacity, larger horizontal displacement, higher displacement ductility, higher energy dissipation, and slower secant stiffness degradation) and the efficiency of FRP composite increased with the sulfate damage level. Also, the FRP composite strengthening technique gave the ability to transform the joint-column regions mode of failure from brittle into a ductile mode of failure through the formation of the plastic hinge in the beam only at a higher level of column axial loads of more than 25%. While the application level of column axial loads less than 25% only enhanced just the ultimate axial load capacity and corresponding deflection.